KINERJA KARYAWAN: KOMPENSASI DAN PROMOSI JABATAN - Sri Langgeng Ratnasari (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
Employee performance is one of the most important factors in an organization, because employee performance is crucial in determining organizational performance. This study aims to determine the effect of compensation on employee performance, the effect of job promotions on employee performance, and the effect of compensation and job promotions on employee performance. This research is a descriptive study through a quantitative approach. The population of this research is the employees of PT. MSP Batam as many as 50 employees. The sampling technique uses census techniques, so the number of samples is 50 employees. The results of testing partially the effect of compensation on employee performance is significant, the effect of job promotions on employee performance has a significant effect, and simultaneously the effect of compensation and job promotions on employee performance has no significant effect.